PENGARUH DEBT TO EQUITY RATIO (DER) DAN PERTUMBUHAN PENJUALAN TERHADAP NILAI PERUSAHAAN PADA PT MAYORA INDAH TBK PERIODE 2013-2022 - Septiani, Sindi; Sanjaya, Rudi (Journal of Research and Publication Innovation, 2024)
This research aims to examine the effect of Debt to Equity Ratio (DER) and sales growth on company value at PT Mayora Indah Tbk listed on the Indonesia Stock Exchange (IDX) for the period 2013-2022. The research method and type of data used in this study are quantitative and secondary data, and processed using the SPSS version 23 application. The sample used is data from the profit and loss, balance sheet, notes to the financial statements and stock overview of PT Mayora Indah Tbk for the period 2013-2022. The data analysis method used is the classical assumption test, multiple linear regression test, hypothesis test and coefficient of determination test (R2). The results of this study indicate that DER has an effect on company value as evidenced by a significant value of 0.003 <0.05 and sales growth has no effect on company value, this is evidenced by a significant value of 0.159> 0.05.